2007
DOI: 10.1038/sj.npp.1301496
|View full text |Cite
|
Sign up to set email alerts
|

Aniracetam Reversed Learning and Memory Deficits Following Prenatal Ethanol Exposure by Modulating Functions of Synaptic AMPA Receptors

Abstract: Specific pharmacological treatments are currently not available to address problems resulting from fetal ethanol exposure, described as Fetal Alcohol Syndrome or Fetal Alcohol Spectrum Disorders (FASD). The present study evaluated the therapeutic effects of aniracetam against cognitive deficits in a well-characterized and sensitive FASD Sprague-Dawley rat model. Ethanol, administered orally at a moderate dose (4 g/kg/24 h; 38% v/v) during the entire course of pregnancy, caused severe cognitive deficits in offs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 84 publications
0
33
0
Order By: Relevance
“…Studies using a variety of alcohol doses, regimens and time periods showed unequivocally that alcohol can disrupt LTP in hippocampus (Izumi et al, 2005; Puglia and Valenzuela, 2010b; Puglia and Valenzuela, 2010a; Richardson et al, 2002; Savage et al, 2010; Sutherland et al, 1997). Interestingly, in this region, pharmacological potentiation of AMPA receptor responses reverses the deficits of alcohol exposed animals in the Morris water maze, a behavior that is dependent on LTP in the hippocampus (Vaglenova et al, 2008). Surprisingly, few studies have investigated the effects of alcohol on LTD.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using a variety of alcohol doses, regimens and time periods showed unequivocally that alcohol can disrupt LTP in hippocampus (Izumi et al, 2005; Puglia and Valenzuela, 2010b; Puglia and Valenzuela, 2010a; Richardson et al, 2002; Savage et al, 2010; Sutherland et al, 1997). Interestingly, in this region, pharmacological potentiation of AMPA receptor responses reverses the deficits of alcohol exposed animals in the Morris water maze, a behavior that is dependent on LTP in the hippocampus (Vaglenova et al, 2008). Surprisingly, few studies have investigated the effects of alcohol on LTD.…”
Section: Discussionmentioning
confidence: 99%
“…Aniracetam positively impacts the pharmacological profile associated with learning and memory by elevating hippocampal acetylcholine, serotonin, glutamate, and dopamine levels [12], [19], [20]. In addition, aniracetam significantly facilitates long-term potentiation (LTP) formation in the hippocampus [21], reverses memory loss [22], reduces anxiety [12], and reverses ethanol-induced brain damage [23], [24]. An important caveat for some of the above behavioral studies is that they were performed in rodent models of disease or using experimentally induced learning deficits and did not explicitly address impacts in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our data indicate that the combination of the high dose of MU and the low dose of MK has an anxiogenic effect only in females. Similarly, Sprague-Dawley adult females, but not males, prenatally exposed to ethanol presented an increase in anxiety-like behaviors as compared to controls (Osborn et al, 1998;Vaglenova et al, 2008). A gender difference was also observed in humans prenatally exposed to ethanol, with females showing higher rates of anxiety than males (Famy et al, 1998).…”
Section: Discussionmentioning
confidence: 56%